Short-Term Soil CO2 Emission and Soil Attributes Under Contrasting Sugarcane Cultivars - Moitinho, Mara Regina [UNESP]; Padovan, Milton Parron; da Silva Bicalho, Elton [UNESP]; Ferraudo, Antonio Sergio [UNESP]; de Bortoli Teixeira, Daniel; de Souza Bahia, Angélica Santos Rabelo [UNESP]; Pinheiro, Daniel Pereira [UNESP]; Vasquez, Llerme Navarro [UNESP]; la Scala Jr., Newton [UNESP] (Springer Nature, 2018)
Agriculture is a great emission source of CO2 into the atmosphere, contributing significantly to the greenhouse effect. Considering the hypothesis that there are differences in soil carbon dynamics due to the distinct physiological and morphological characteristics of sugarcane cultivars, the aim of this study was to characterize the short-term soil CO2 emission associated with soil attributes in agricultural areas under cultivation of five sugarcane cultivars. The experiment was conducted in an area of high-clay Oxisol (Hapludox, USDA Soil Taxonomy) located at the Cerrado biome, Midwestern region of Brazil. Over the course of 20 days, ten measurements of soil CO2 emission (FCO2), soil temperature (Ts), and soil moisture (Ms) were carried out. Subsequently, soil samples were collected at a depth of 0–0.20 m to determine soil physical and chemical attributes. In timescale, FCO2, Ts, and Ms varied depending on the amount of straw produced by each cultivar. The cultivars RB935608, RB935744, and SP832847 induced a higher soil CO2 emission since they are associated with controlling factors of the primary CO2 production process (higher organic matter content and lower C/N ratio in the soil). Thus, strategies to reduce greenhouse gas emissions in agriculture, such as the choice of sugarcane cultivars that provide lower soil CO2 emissions, are essential to mitigate important environmental issues such as the global warming.
Keywords: Multivariate analysis; Saccharum spp.; Soil attributes; Soil respiration